English English - Aprianti, Yuli; Supriatna, Nana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Students' diverse learning needs require teachers to be able to determine learning strategies. Teachers must be able to recognise and understand students' intelligence and develop it for future success. Differentiated learning is an attempt to adjust the learning process in the classroom to meet the individual learning needs of each learner. Differentiated learning is flexible, meaning learners learn with peers of similar or different abilities according to their strengths and interests. Gardner's theory states that intelligence is not only Intelligence Quotient (IQ) Intelligence is not only about a child's high IQ level, but there are other aspects of intelligence found in children. Every child is unique, they have different ways of absorbing and processing the information they receive. The research method used is qualitative with observation and interview techniques. This research was conducted on teachers and students of grade 4 elementary school. The results showed that differentiated learning is able to facilitate the needs of diverse students. Through differentiated learning all students' learning needs can be accommodated so that it has an impact on the development of students' multiple intelligences.